Self-efficacy dan Employability: Peran Mediasi Achievement Motivation pada Mahasiswa Tingkat Akhir yang akan Memasuki Dunia Kerja - Wulandari, Voni; Zona, Mega Asri; Marna, Jean Elikal; Oknaryana, Oknaryana (Jurnal Ecogen, 2024)
This research aims to find the influence of self-efficacy and achievement motivation on employability. This research is causal research with cross-sectional data. The respondents used were 95 final-year students in the Faculty of Economics and Business, Universitas Negeri Padang who were chosen using the cluster proportional random sampling technique. Data collection using a questionnaire with a Likert Scale. The data was then analyzed using SmartPLS 4 software.  The results of data processing in this research indicate that: (1) self-efficacy has a positive and significant effect on employability (2) self-efficacy has a positive and significant effect on achievement motivation (3) achievement motivation has a positive and significant effect on employability (4) achievement motivation has a positive and significant effect on employability through achievement motivation.